Passive Drip Stain Formation Dynamics of Blood onto Hard Surfaces and Comparison with Simple Fluids for Blood Substitute Development and Assessment1, 2. Issue 1 (22nd November 2016) - Stotesbury, Theresa; Taylor, Michael C.; Jermy, Mark C.
Abstract: The spreading dynamics of blood dripping onto hard surfaces is compared to two spreading models. Samples of human blood, porcine blood, and Millipore ® water were dripped onto cardboard, foamcore, and glass surfaces in low velocity passive drip simulations. Final stain diameter, the total number of spines and scallops, and angle of impact were measured and analyzed. Spreading is best predicted by applying the concept of effective viscosity to the Scheller and Bousfield ( R 2 = 0.91) and Roisman ( R 2 = 0.89) spreading models. In the tested conditions, blood spreads with Newtonian tendencies; however, has quantifiable differences in stain appearance to Newtonian fluids like water. This is encouraging for the development of water‐based fluids as synthetic blood substitutes (SBSs). The work presents an assessment platform to quantify and score the performance of simple water‐based fluids using final stain diameter (6 points) and number of spines and scallops (6 points) at six dripping heights between 20 and 120 cm. The angle of impact of a stain alone is not a sensitive measure of SBS performance, but stain formation scores the SBS's performance with another 1 point. Together these features generate a quantitative relative ranking system, of a maximum possible 13 points, that can be used to support the use of a particular fluid for the creation of a drip stain. The performance of twenty simple fluids in the simulated dripping assessment test is described.